Issue of Federal System in Nepal - Ghimire, Tara Nath (Tribhuvan University Journal, 2019)
Federal process of Nepal has been guided by some major factors such as elimination of discrimination, equal regional development and political participation. Federalism has been a crucial issue of modern Nepal. The issue of federalism has not been guided by remote past as a vital demand because Nepal has adopted a long history of unitary system. But some regional and marginalized groups have been demanding it since 1950, who were struggling against discriminations. Federalism was not documented even in an initiate part of Interim Constitution 2006. It was also not agenda of Maoist Party which they had put in forty points demand letter. It wasn’t materialized till peoples’ movement second. It is supposed that federalism can bring miraculous modification as to solve problems of inequity and marginalization than in the unitary system. Some political parties have documented in their manifesto that federal system is only the alternation for prosperity in Nepal. But it might be incorrect supposition. Long route of unitary system of Nepal was led by few elites, who were specially professed Hindus. Monarchy was also surrounded by prevailing castes. Due to these various reasons conflict began in Nepal which has developed as transitional movement of chronic infection. The issue of federal system is emerged by those who are struggling against discriminations and they want to abolish all kind of social discriminations, problems of regional, religion, gender, cast, and poverty. Aspirations of ownership of all segments and development of nation have guided to make federal state in Nepal.